Genomic characterization of bZIP gene family and patterns of gene regulation on Cercospora beticola Sacc resistance in sugar beet (Beta vulgaris L.) - Yin, Xiao; Liu, Yu; Gong, Yunhe; Ding, Guangzhou; Zhao, Chunlei; Li, Yanli (Frontiers in Genetics, 2024)
Sugar beet (Beta vulgaris L.) is one of the most important sugar crops, accounting for nearly 30% of the world's annual sugar production. And it is mainly distributed in the northwestern, northern, and northeastern regions of China. However, cercospora leaf spot (CLS) is the most serious and destructive foliar disease during the cultivation of sugar beet. In plants, the bZIP gene family is one of important family of transcription factors that regulate many biological processes, including cell and tissue differentiation, pathogen defense, light response, and abiotic stress signaling. Although the bZIP gene family has been mentioned in previous studies as playing a crucial role in plant defense against diseases, there has been no comprehensive studies or functional analysis of the bZIP gene family in sugar beet (Beta vulgaris L.) with respect to biotic stresses. In this study, we performed a genome-wide analysis of bZIP family genes (BvbZIPs) in sugar beet to investigate their phylogenetic relationships, gene structure and chromosomal localization, as well as the functions of BvbZIPs in relation to biotic stresses. Gene expression analysis showed that 6 BvbZIPs were significantly differential expressed by Cercospora beticola Sacc (C. beticola) infection. It is speculated that these BvbZIPs are candidate genes for regulating the response of sugar beet to CLS infection. The analysis of cell ultrastructure and expression of Areb1 showed that the differential expression of Areb1 (BvbZIP37) regulates the stomatal closure of sugar beet leaves under the C. beticola stress. In addition, we further confirmed that the protein encoded by the SA signaling pathway-related gene BVRB_9g222570 in high-resistant varieties was PR1, which is closely related to systemic acquired resistance. One of the protein interaction modes of JA signal transduction pathway is the response of MYC2 transcription factor caused by JAZ protein degradation, and there is a molecular interaction between JA signal transduction pathway and auxin. Despite previous reports on abiotic stresses in sugar beet, this study provides very useful information for further research on the role of the sugar beet bZIP gene family. The above research findings can promote the development of sugar beet disease resistance breeding.